Filter banks system in frequency domain for digital imaging segmentation in controlling crop growth (2014)
This paper presents a strategy for improving the measurement of plant growth, based on digital image processing. This strategy facilitates the segmentation of the regions of interest. We used the filter bank technique in the frequency domain, because the frequency domain has presented positive results in order to highlight the textures of growing plants. We offer a tool to automatically measure the size of each plant. The proposed tool is oriented to systems analysis and the control of crop growth.